ANALYSIS OF THE INFLUENCE OF PROFITABILITY, LIQUIDITY AND RATIO LEVERAGE ON COMPANY VALUE IN FINANCING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2019 - 2023: ANALYSIS OF THE INFLUENCE OF PROFITABILITY, LIQUIDITY AND RATIO LEVERAGE ON COMPANY VALUE IN FINANCING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2019 - 2023 - Almarethania, Miftahul Janah; Zulkarnain, Iskandar (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This research aims to determine the effect of profitability, which is proxied by Return On Equity (ROE), liquidity, which is proxied by Current Ratio (CR), and Leverage, which is proxied by Debt to Equity Ratio (DER), on company value by proxy Price to Book Value ( PBV) in Financing Companies Sub-Sector companies on the Indonesian Stock Exchange for the 2019-2023 period. This research uses quantitative methods. The data used in this research is secondary data. The population in this research are finance companies listed on the Indonesia Stock Exchange, with a research period from 2019 to 2023, totaling 14 finance companies. The sample selected using the purposive sampling method consisted of 11 finance companies. Partial research results found that Profitability (ROE) had no significant effect on company value, Liquidity (CR) had no effect on company value, and Leverage (DER) has a significant effect on company value.